Egypt Economic Monitor, December 2021 : The Far-Reaching Impact of Government Digitalization - World Bank (World Bank, Washington, DC, 2022)
The Egyptian economy continues to show resilience through the COVID-19 pandemic, due to the macroeconomic and energy sector reforms implemented in recent years, along with measures to ease monetary conditions, provide selected sectoral support and mobilize external financing. Real GDP growth and foreign income activities started recovering since Q4-FY2020/21. However, global COVID-related challenges and an uneven recovery across the world continue to restrain the rebound. Foreign reserves remain ample, but the widened current account deficit has increased financing requirements. Fiscal consolidation has helped bring down the budget deficit-to-GDP ratio. Yet, fiscal space remains constrained by the interest burden and below-potential revenue-mobilization. Egypt is expected to resume pre-pandemic growth in FY2021/22 as the COVID-situation gradually improves. Further advancement of structural reforms is critical to sustain the recovery, drive productivity growth and generate high-earning job opportunities. The Focus Chapter in this report is dedicated to the topic of government digitalization; a key priority of the country’s national structural reform program. Egypt is currently at a relatively elevated level of government digitalization, according to international indices such as the United Nations E-Government Development Index, as well as the newly constructed World Bank GovTech Maturity Index. For the recent digitalization efforts to realize their potential and further enhance governance and public service delivery, continued reforms require focus on: (1) The roll-out of ‘end-to-end’ digital solutions (whereby digital transformation occurs in every step throughout a given governmental process), ensuring the integration and inter-connectedness (inter-operability) of related government systems, (2) Complementing digital transformation with a continued simplification and streamlining of government processes. (3) Strengthening the foundations of the “Digital Economy” in Egypt is crucial to effectively leverage technologies for a more efficient government, and for large-scale uptake by individuals and businesses. This will require (3-a) Continuous investments in digital infrastructure across the country to ensure uninterrupted availability of essential digital government services and universal access to high quality internet, (3-b) Promotion of digital skills, (3-c) Incentivizing use of digital financial services, and (3-d) Ensuring an overall conducive legal and regulatory framework for the digital transformation of the economy.